2001
DOI: 10.1183/09031936.01.17202200
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of airway obstruction and patient-reported endpoints in clinical studies

Abstract: To establish the correlation among asthma efficacy parameters over a long period, data from over 1500 patients in two one-year asthma clinical trials with montelukast, a Cys-LT1 antagonist, were analysed. Airway obstruction measurements, forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF), were measured at clinic visits. Patients recorded daytime symptom score, "as-needed" bagonist use, and PEF on a daily basis.Relationships among these parameters at baseline and during the one-year tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 8 publications
4
31
0
1
Order By: Relevance
“…This is particularly likely if the patient has been using as-needed β-agonist inhalers. In a large study of more than 1,500 patients in clinical trials, correlation coefficients between airway obstruction (FEV 1 and PEF) and patient-reported end points (asthma symptoms and as-needed β-agonist use) was low (-0.13 to -0.23) (Shingo et al 2001). The within-subject Spearman rank correlations between evening PEF and ordinal symptom score in the present study ranged widely, from 0.46 to -0.62 (mean, -0.07).…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly likely if the patient has been using as-needed β-agonist inhalers. In a large study of more than 1,500 patients in clinical trials, correlation coefficients between airway obstruction (FEV 1 and PEF) and patient-reported end points (asthma symptoms and as-needed β-agonist use) was low (-0.13 to -0.23) (Shingo et al 2001). The within-subject Spearman rank correlations between evening PEF and ordinal symptom score in the present study ranged widely, from 0.46 to -0.62 (mean, -0.07).…”
Section: Discussionmentioning
confidence: 98%
“…Individuals with impaired lung function do not always have more respiratory symptoms, but a correlation between these two has already been reported (26). The presence of chemical vapours, fumes, odours and other mineral dusts, should also be taken into account, as they may contribute to the respiratory effects.…”
Section: Discussionmentioning
confidence: 99%
“…This intuitively makes sense to the clinician, but is difficult to support scientifically because numerous studies have shown that there is poor correlation between reporting of asthma symptoms and objective measures of lung function. 36,38,39 Other observations make it difficult to support scaling symptoms and lung function in the same way. Patients cannot reliably predict changes in their lung function based on the symptoms they experience 40 and physicians cannot accurately predict lung function from examinations of patients with asthma.…”
Section: Asthma Severity Categorization Methods In Current Guidelinesmentioning
confidence: 99%